The Use of Google Sites in Teaching Descriptive Text in EFL Classroom - Ryan Rayhana Sofyan; Nur Aulia; Abdullah (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study aims to examine (1) the effectiveness of Google Sites in enhancing students’ descriptive writing skills and (2) students’ perceptions of using Google Sites for learning English. A quasi-experimental method was used, involving questionnaires and writing tests. The study included 50 students: 25 in the experimental was Class X TSM (Teknik Sepeda Motor) using Google Sites and 25 in the control group was Class X TKR (Teknik Kendaraan Ringan) using conventional methods. Results showed that Google Sites significantly improved writing skills. The experimental group's mean score increased from 70.20 (pre-test) to 90.80 (post-test), while the control group improved from 66.96 to 88.40. These findings confirm Google Sites as an effective learning tool. Aside from that, the average score for the students' questionnaire replies was 46.24. According to the interval scale, the mean score of students' thoughts on using Google Sites to study descriptive texts was extremely favorable. As a result, using Google Sites effectively improves students' descriptive writing skills, and the majority of students see Google Sites proved to be an effective learning tool for English, especially when it comes to producing descriptive texts.